DESCRIPTION OF PULP TREATMENT AND POST PULP TREATMENT MATERIALS IN BPJS AND UNINSURED PATIENTS IN THE DENTAL CLINIC, IDAMAN DISTRICT HOSPITAL, BANJARBARU - Juli Harnida Purwaningayu; Rosihan Adhani; Diana Wibowo (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACT: Background: Badan Penyelenggaran Jaminan Sosial (BPJS) is a form of the implementation of the National Health Insurance which is tasked to ensure the maintenance of health for all Indonesians. But many people are not satisfied with BPJS. Kurniawan research in 2015, treatment measures (aspects of assurance) were significantly different between uninsured patients and BPJS patients. Idaman Hospital, Banjarbaru is a type C hospital owned by the city government, as an advanced level health facility in implementing BPJS. Pulp treatment is a kind of treatments in dental and mouth which covered by BPJS. Purpose: To know the description of pulp treatment and post pulp treatment materials in BPJS and uninsured patients in Idaman District Hospital, Banjarbaru. Methods: A descriptive observational study with retrospective secondary data collect from patient registers in January-December 2018. Results: Outpatients that insured by BPJS were 78.84% and uninsured were 21.10%. The use of dental pulp treatment materials was arsenic with 13.6% in BPJS patients and 6.6% in uninsured patients, formocresol with 21.5% in BPJS patients and 5.6% in uninsured patients, cresophene 20.42% in BPJS patients and 3.76% in uninsured patients, eugenol 2,81% in BPJS patients and 2.35% in uninsured patients. The most common used post-pulp treatment materials were 16.6% GIC for BPJS patients and 6.09% in uninsured patients, while composites were only 0.23% for both. Conclusion: Dental pulp treatment materials in BPJS and uninsured patients are arsenic, formocresol, cresophene and eugenol, while post pulp treatment materials are GIC and composite.Keywords: BPJS, Pulp Treatment, Uninsured Patients